81 Attitude towards and factors affecting uptake of population based BRCA testing in ashkenazi jews: a cohort study. (18th September 2019) - Manchanda, R; Burnell, M; Gaba, F; Sanderson, S; Loggenberg, K; Gessler, S; Wardle, J; Side, L; Desai, R; Brady, A; Dorkins, H; Wallis, Y; et al.
Abstract : Objectives: To evaluate the factors affecting interest, intention, uptake, and attitude towards unselected population-based BRCA -testing in the Ashkenazi Jewish (AJ) population. Methods: Design: Cohort-study set within recruitment to the GCaPPS-trial (ISRCTN73338115 ). AJ women/men >18-years, from the North-London AJ-population were recruited through self-referral. AJ-women/men underwent pre-test counselling for BRCA -testing through recruitment clinics (clusters). Consenting individuals provided blood-sample for BRCA -testing. Socio-demographic/family-history/knowledge/psychological well-being data along-with benefits/risks/cultural-influences (18-item-questionnaire measuring 'attitude') were collected. 4-item likert-scales analysed initial 'interest' and 'intention-to-test' pre-counselling. Uni-&-multivariable logistic-regression-models evaluated factors affecting uptake/interest/intention-to undergo BRCA -testing. Statistical inference was based on cluster robust standard-errors and joint Wald-tests for significance. Item-Response-Theory and graded-response-models modelled responses to 18-item questionnaire. Main Outcome Measures: Interest, intention, uptake, attitude towards BRCA -testing Results: 935 AJ women (67%) and men (33%) underwent pre-test genetic-counselling (mean-age=53.8(S.D=15.02) years). Pre-counselling 96% expressed interest but 60% had clear intention-to undergo BRCA -testing. Subsequently 88% opted for BRCA -testing. BRCA -related knowledge (p=0.013) and degree-level education(p=0.01) were positively and negatively (respectively) associated with intention-to-test. Being married/cohabiting had four-fold higher-odds for BRCA -testing uptake (p=0.009). Perceived benefits were associated with higher pre-counselling odds for interest and intention-to undergo BRCA -testing. Reduced uncertainty/reassurance were the most important factors contributing to decision-making. Increased importance/concern towards risks/limitations (confidentiality/insurance/emotional-impact/inability to prevent cancer/marriage-ability/ethnic-focus/stigmatization) were significantly associated with lower-odds of uptake-of BRCA -testing, and discriminated between acceptors and decliners. Having children had stronger (p=0.005) while male-gender/degree-level-education (p=0.001) had weaker, attitudes towards BRCA -testing. Conclusions: BRCA testing in the AJ population has high acceptability. Pre-test counselling increases awareness of disadvantages/limitations of BRCA -testing, influencing the final cost-benefit perception and decision-making on undergoing testing.